Distributed secondary controller to ensure proportional sharing of reactive power in AC microgrid - Shirazul Islam (16904535) (2022)
In an ac microgrid, reactive power sharing accuracy is affected due to unequal values of interconnecting cable impedances. To resolve this issue, secondary controllers are used to compensate the effect of cable impedances. Various types of secondary controllers are suggested in the literature which includes linear proportional plus integral (PI) controllers to minimize the difference in reactive power sharing created by conventional E − Q droop law. The reference value of the PI controller is the average value of reactive powers supplied by the sources. When the PI controller is used to minimize the difference between the actual and reference value of reactive power, the difference between the algebraic sum of reactive powers supplied by the sources and the reactive powers demanded by the loads has a nonzero value. Therefore, the performance of these controllers becomes poor in the case of ac microgrid having sources of unequal ratings. To resolve this issue, a proportional reactive power-sharing (PRPS) controller-based distributed secondary controller is proposed in this paper. The PRPS controller modifies the droop gain of the E − Q droop control loop of each source in such a way that each source supplies reactive power equal to its proportional value of reactive power. The proportional value of reactive power supplied by each source is the power when the equivalent output impedance of all sources as seen by the loads are identical. The key advantage offered by the proposed controller is the accurate reactive power-sharing in the case of ac microgrid having sources of unequal ratings. The proposed controller ensures zero value of the difference between the algebraic sum of reactive powers supplied by the sources and the reactive powers demanded by the loads. This ensures accurate sharing of reactive power among the sources. The validation of the proposed controller is carried out for islanded mode of operation of ac microgrid. Further, the proposed controller requires of low bandwidth communication for its implementation. The effect of the proposed controller on the stability of the system is demonstrated using reduced order small-signal model. The effect of communication delay on the performance of the system is analyzed with the help of roots locus plots. To validate the efficacy of the proposed controller, detailed simulation studies are carried out in Matlab/Simulink. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2022.05.014